Using corticosteroids to treat sudden sensorineural hearing loss in pregnancy: A case report and literature review - Peter Khamvongsa; Naiya Patel; Ayesha Aziz Ali; Nikita Bodoukhin; Octavio Carreno (Elsevier, 2020)
Sudden sensorineural hearing loss (SSNHL) can manifest in pregnancy, but very few cases of SSNHL in pregnancy have been reported and none has been reported in the United States. Additionally, there are no established guidelines for how to treat SSNHL in pregnancy. The purpose of this report is to describe how SSNHL presents in pregnancy, to evaluate other etiologies and discuss current treatment options. A 35-year-old parous woman at 22 weeks of gestation, with a 2-week history of left-sided hearing loss, was shown to have a speech recognition threshold of 70 dB in her left ear. Otolaryngology confirmed the diagnosis of SSNHL. The patient was prescribed an oral prednisone taper that helped alleviate the hearing loss. She had an uncomplicated delivery and treatment with corticosteroids had no adverse consequences for the patient. After ruling out etiologies of SSNHL, corticosteroids may be used safely and efficaciously to treat SSNHL during the second trimester of pregnancy.